IMPROVEMENT OF THE SECURING A CLAIM IN LATVIAN LEGAL POLICY PLANNING DOCUMENTS - Gvozdevičs, Andrejs (SOCIETY. INTEGRATION. EDUCATION. Proceedings of the International Scientific Conference, 2021)
In the framework of his scientific work, the author makes a research on the problematic aspects of the procedure of the securing a claim, including in legal policy planning documents, which  play an important role in the development of the procedure of the securing a claim. Topicality and novelty of the research are reflected in the fact that until now in the legal doctrine weren’t made depth and extensive researches of the role of legal policy planning documents in solving problems of the securing a claim. The aim of the research was to analyze legal policy documents regarding to the procedure of the securing a claim in order to identify plans of the public administration to improve the procedure of the securing a claim and civil procedure in general. In the present research, using the analytical, descriptive and deduction / induction method, was analyzed the normative acts and legal policy planning documents of the public administration. Results: Analyzing the legal policy planning documents related to the procedure of the securing a claim, it has been established that public administration has not planned to carry out reforms of the provision of the securing a claim, except for the planned regulation on the possibilities of the securing claim in the non-material nature claims, which, unfortunately, is still not fulfilled. Conclusions: The public administration should clearly define in legal policy documents the objectives and tools for making modern and effective civil procedure in general and the procedure of the securing a claim in particular.